Avaliação da função atrial esquerda por meio da ecocardiografia feature tracking bidimensional em cães assintomáticos com degeneração mixomatosa da valva mitral - Coelho, Mariana de Resende (2018)
Among the acquired heart disease in dogs, myxomatous mitral valve disease (MMVD) is the most prevalent. Echocardiography is the complementary examination used to obtain noninvasively diagnosis of MMVD, as well as to predict its prognosis. New tools such as feature tracking echocardiography (2D-FTI) has been evaluated for the potential to provide early prognostic of cardiac alterations, since it allows obtain myocardial deformation by means of variables Strain (St) and Strain Rate (StR). The evaluation of left atrial function is essential since the left atrium enlargement due to mitral valve regurgitation may be considered a prognostic factor and is used to determine the therapeutic management of the patient. The present study evaluated the left atrial function in dogs with MMVD asymptomatic by means of 2D-FTI. For this, 80 dogs were evaluated divided into three groups: Group 1 composed of healthy dogs (n = 21); Group 2 comprised dogs with MMVD and asymptomatic class B1 (n = 30) and Group 3 comprised dogs with MMVD and asymptomatic class B2 (n = 29). The values of St and StR for the atrial functions (reservoir, conduction and contraction) were obtained in the apical four-chamber left-side view. In general, there was no statistically significant difference for the StR variable in the different atrial functions, but St (contraction strain) was significantly lower in class B2 than in the control group (12.92 ± 4.54 x 16.69 ± 5.74, p = 0.014). The atrial diastolic volume index (iVdA) measured by means of 2D-FTI was significantly higher in class B2 than in the control group (1.31 ± 0.95 x 0.96 ± 0.31, p = 0.038), as well as for the atrial cardiac index (iCA) was also higher in class B2 (102.38 ± 80.18 x 78.19 ± 33.38, p = 0.030). In the intraobserver assessment, the correlation was high for all volume variables, St, and StR, but some variables presented a wide confidence interval (CI). In the interobserver assessment, the correlation was high only for the volume variables (in diastole and systole), for others, the correlation was low to moderate and some also presented a broad CI. Thus, it is concluded that MMVD causes alteration in atrial function, especially in the contraction phase even in asymptomatic animals and that 2D-FTI echocardiography is a sensitive and early method for the detection of left atrial dysfunction.